Increase in newly diagnosed type 1 diabetes and serological evidence of recent SARS-CoV-2 infection: Is there a connection? - Denina, Marco; Trada, Michela; Tinti, Davide; Funiciello, Elisa; Novara, Chiara; Moretto, Martina; Rosati, Sergio; Garazzino, Silvia; Bondone, Claudia; De Sanctis, Luisa (Frontiers in Medicine, 2022)
Several studies have investigated the correlation between the COVID-19 pandemic and the onset of type 1 diabetes (T1D) in children, reporting an increased incidence of T1D and severe diabetic ketoacidosis (DKA). This study aimed to investigate the infection by SARS-CoV-2 in children with newly-diagnosed T1D to explore a possible link between SARS-CoV-2 infection, T1D and DKA. Thirty-nine children with a T1D new onset between October 15, 2020, and April 15, 2021, were enrolled. SARS-CoV-2 infection was investigated through a polymerase chain reaction on the nasal swab, dosage of specific antibodies, and an anamnestic question form. 23% of them had antibodies directed towards SARS-CoV-2, and five had a history of recent SARS-CoV2 infection in themselves or in their family. No molecular swabs were positive. Compared to the general paediatric population, the overall incidence of COVID-19 was 5.6 times higher in the T1D patients' group (p <0.00001). Referring only to the cases in the metropolitan area, we find a net increase in the incidence of T1D compared to the five years preceding our study, by 50% compared to the same months in 2016/2017 and 2017/2018, by 69% compared to 2018/2019 and by 77% compared to 2019/2020. The same trend was observed regarding DKA cases. The attributable risk of the pandemic cohort compared to the previous year is 44%. The abnormal disproportion of SARS-CoV-2 infection between children with T1D and the paediatric reference population, with a ratio of 5.6, appears to support the causative role of SARS-CoV-2 in triggering the immune response underlying diabetes, as often described for other viral infections. The difficulty accessing care services during the pandemic, with a consequent diagnosis delay, does not justify the increase in observed T1D cases, which appear to be directly linked to the pandemic. The acceleration of the immune process provoked by SARS-CoV-2 may play a suggestive role in the development of T1D with DKA. Multicentre studies are needed to deepen and fully understand the pathophysiological link between SARS-CoV-2 and the onset of T1D in children.